Customer Perceptions of Digital Halal Certification and Its Implications for MSME Product Purchasing Decisions - Ilham Teruna Bakti; Cicih Ratnasih (Greenation Research & Yayasan Global Resarch National, 2025)
This study analyzes consumer perceptions of digital halal certification for MSME products and its impact on purchasing decisions. The research method uses a quantitative approach with survey techniques to 385 Muslim consumers in Central Java. The results show that 73.2% of respondents have positive perceptions of digital halal certification for MSMEs. The main factors influencing consumer perceptions include ease of digital verification (78.5%), trust in certification institutions (71.8%), and level of understanding of the certification process (69.3%). Regression analysis shows that positive perceptions of digital halal certification significantly influence purchasing decisions with a coefficient of determination value of 0.652. This research contributes to MSMEs in understanding consumer preferences for digital halal-certified products and their implications for marketing strategies.